2009
DOI: 10.1530/eje-09-0677
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of genetic variants of phosphodiesterase 11A in acromegalic patients

Abstract: Objectives: Aberrant cAMP signaling is involved in the pathogenesis of somatotropinomas. The aim of the study was to screen acromegalic patients for the presence of variants of phosphodiesterase type 11A (PDE11A) gene, which have been recently identified in adrenocortical and testicular tumors. Subjects and methods: We sequenced the PDE11A gene-coding region in 78 acromegalic patients and 110 controls. Immunohistochemistry for PDE11A was performed in a subgroup of adenomas and normal pituitary samples. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…These nonsense/missense PDE11A variants were also found in about a fifth of GH-secreting adenomas, with a frequency slightly higher with respect to controls (Peverelli et al 2009a). However, in these tumors, the WT allele was maintained, with a consequent normal expression of this enzyme, and mutated patients showed no significant clinical phenotype, except a tendency toward greater tumor dimensions and suprasellar extension with respect to WT patients, suggesting that these variants might only marginally contribute to the development of somatotropinomas.…”
Section: Inactivating Mutations Of Pdes In Patients With Other Camp-dmentioning
confidence: 89%
See 1 more Smart Citation
“…These nonsense/missense PDE11A variants were also found in about a fifth of GH-secreting adenomas, with a frequency slightly higher with respect to controls (Peverelli et al 2009a). However, in these tumors, the WT allele was maintained, with a consequent normal expression of this enzyme, and mutated patients showed no significant clinical phenotype, except a tendency toward greater tumor dimensions and suprasellar extension with respect to WT patients, suggesting that these variants might only marginally contribute to the development of somatotropinomas.…”
Section: Inactivating Mutations Of Pdes In Patients With Other Camp-dmentioning
confidence: 89%
“…Up to now, 11 subfamilies of PDEs, which differ in structure, enzymatic properties, sensitivity to inhibitors, and expression, have been characterized, each subfamily including distinct genes that, in turn, generate several transcripts by alternative splicing and/or the use of multiple promoters (Bender & Beavo 2006). Among these different isoforms PDE1A, PDE2A, PDE4(A,B,C,D), PDE8B, and PDE11A are the most expressed in the pituitary (Michibata et al 2001, Persani et al 2001, Peverelli et al 2009a, Stephenson et al 2009, Lennox et al 2011. PDEs are activated by cAMP both by phosphorylation and gene expression induction.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced cAMP degradation caused by mutations in PDE11A and PDE8B, coding for members of the phosphodiesterase (PDE) family, have been involved in adrenocortical hyperplasia, adenomas, and cancer as well as in testicular germ cell tumors (23,24). However, genetic variants of PDE11A4 contribute only marginally to the development of GH-secreting adenomas (25). Recently, mutations affecting the gene encoding the catalytic subunit a of the PKA (PRKACA) have been reported in a large proportion of cortisol-secreting adrenocortical adenomas (26,27,28,29,30), resulting in an increased PKA activity (31).…”
mentioning
confidence: 99%
“…We recently showed that inactivating PDE11A sequence variants appear to predispose to not only adrenocortical tumors (ADT) but also testicular germ cell tumors (TGCT) (6 -8). The effect of PDE11A genetic variants appears to be limited to steroidogenic tissues, because in a recent study of sporadic GH-secreting tumors, the frequency of PDE11A missense variants was found only slightly increased compared with that in control patients (9). In vitro studies of PDE11A sequence variants that were predicted in silico to have an effect on function showed that indeed enzymatic activity was decreased, leading to higher levels of cAMP and/or cGMP in HeLa or HEK293 cells (5,6,8).…”
mentioning
confidence: 99%